2018
DOI: 10.1007/s40122-018-0100-2
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Chronic Musculoskeletal Pain: Central and Peripheral Effects of Diclofenac

Abstract: Diclofenac is widely used to manage chronic inflammatory and degenerative joint diseases such as osteoarthritis (OA), rheumatoid arthritis (RA), ankylosing spondylitis, and extra-articular rheumatism. Its various mechanisms of action make it particularly effective in treating nociceptive pain, but it is also an alternative for treating spinal and chronic central pain. Osteoarthritis and rheumatoid arthritis are the most frequently encountered arthritic conditions in adults. The management of nociceptive pain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 98 publications
(113 reference statements)
0
28
0
Order By: Relevance
“…The MIA injection causes immediate onset of mechanical hyperalgesia (8,9), altered weight bearing (10), and reduction in mobility (11), all of which are associated with the early inflammatory phase (days 0-7) of OA. This is then followed by a more persistent allodynia, typical in late-phase OA (days [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Pain-like behaviors increase in a dose-dependent manner, with late-phase hypersensitivity typically observed with higher doses of MIA (12).…”
Section: Introductionmentioning
confidence: 99%
“…The MIA injection causes immediate onset of mechanical hyperalgesia (8,9), altered weight bearing (10), and reduction in mobility (11), all of which are associated with the early inflammatory phase (days 0-7) of OA. This is then followed by a more persistent allodynia, typical in late-phase OA (days [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Pain-like behaviors increase in a dose-dependent manner, with late-phase hypersensitivity typically observed with higher doses of MIA (12).…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs such as ibuprofen, ketoprofen, salicylate, naproxen and diclofenac have been used for pain management along with physical therapy [ 11 , 15 ]. Diclofenac has shown the most efficacy, as COX-1/2 inhibitors lead to the downregulation of prostaglandin-2 and associated inflammatory cytokines such as us IL-1β, TNF α, along with MMP 13, a disintegrin and metalloproteinase with thrombospondin-1 domains 4 and 5 [ 13 , 14 , 34 , 41 ]. Systemic application of long-term use NSAIDs can cause severe damage to the kidney, liver and gastrointestinal complications, while only providing short-term pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…The topical application of NSAIDs reduces the systemic risks but has reduced efficacy due to limited penetration through the skin [ 12 ]. Diclofenac is one of the most common NSAIDs used [ 13 , 14 ]. It inhibits COX-1 and -2, the underlying expression of prostaglandin-2 and thromboxane synthesis approximately 3–1000× more than other NSAIDs [ 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CFA is often used in the induction of various chronic inflammatory pain models. The study of peripheral and central mechanisms of inflammatory pain has been focused by the international research (Xu et al, 2010; Atzeni et al, 2018; Rosas et al, 2018). Numerous studies have shown that many peripheral and central nervous structures and a variety of chemicals are involved in the formation and regulation of inflammatory pain (Vane and Botting, 1995).…”
Section: Introductionmentioning
confidence: 99%